Reply to "Comment on ' α decay in the complex-energy shell model'" - Id Betan, Rodolfo Mohamed (2016)
We reply to the Comment by Lovas, which concerns the shell model calculations of the α-decay width of Po212. In the Comment, the author claims that the α-formation amplitudes obtained in our work "look unusual." Here we reaffirm the results and conclusions of our original article.